LABORATORY EVALUATION OF MOISTURE DAMAGE AND DURABILITY OF HOT MIX ASPHALT (HMA) - G. Ahmed, Namir; M. AL-Badran, Yasir; M. Azeez, Doaa (Journal of Engineering and Sustainable Development, 2017)
The increasing of road material demand particularly on mineral filler and additives has been followed-up by finding the new alternative materials. Local materials such as Portland cement, and lime may potentially use to substitute current need. Therefore, it is essential to study the performance and durability of these materials in HMA mixture. To find the durability index, the specimens are immersed around 0 (unconditioned) to 14 days at 60ºC and tested by using Marshall and ITS tests. Based on Marshall test, the index values for mixes variations; DCF, DPC, DL, DPF, and DC are found to be; 42.965%, 36.59%, 36.582%, 35.68%, and 33.42%, respectively.